Ocular Toxicity Secondary to Asclepias physocarpa: The Balloon Plant - Susana Pina; Catarina Pedrosa; Cristina Santos; Bernardo Feijóo; Peter Pego; Cristina Vendrell; Maria João Santos; Isabel Prieto (Case Reports in Ophthalmological Medicine)
We report a case of a 65-year-old woman with symptoms of blurred vision and ocular irritation a few hours after accidental contact of the right eye with Asclepias physocarpa milky latex. Observation showed a diffuse conjunctival hyperemia and stromal corneal edema with Descemet’s membrane folds. Recovery was fast and apparently complete in less than one month. However, specular microscopy at 6-months follow-up showed an abnormal endothelial morphology as sequelae, suggesting this condition is not as innocuous as it has been suggested.